THE COLORFUL WORLD OF POLLINATION: EXPLORING THE INTERACTIONS BETWEEN PLANTS AND POLLINATORS - Irshad Ahmad Wani; Zakir Hussain Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Pollination is a crucial ecological process that enables the reproduction of a wide range of plant species, ensuring biodiversity, ecosystem stability, and food security. This paper explores the dynamic interactions between plants and their pollinators, including the evolutionary mechanisms shaping these relationships. It discusses the various types of pollinators, such as insects, birds, mammals, and wind, and examines plant adaptations that facilitate successful pollination. Furthermore, the paper investigates the ecological significance of pollination, highlighting its role in sustaining food webs and supporting agricultural systems. The growing threats to pollinator populations, including habitat loss, pesticide use, and climate change, are also addressed, emphasizing the urgency of conservation efforts. Understanding the complex web of interactions between plants and pollinators is critical to protecting these essential ecological services and ensuring the health of global ecosystems.